Fixed Point Results for Cyclic Contractions in Partial Symmetric Spaces - Rathee, Savita; Gupta, Priyanka (Communications in Mathematics and Applications, 2021)
In this paper, we prove fixed point results for various cyclic contractions in partial symmetric spaces. Our results generalize the fixed point results of Asim et al. (Fixed point results in partial symmetric spaces with an application, Axioms 8(13) (2019), 1 – 15) proved for the class of partial symmetric spaces for various contractions. Also, we provide an example in the support of proved result.